Design of an anaerobic biodigester model as an alternative for methane generation - Ángel Canales-Gutiérrez; Blanca Jacqueline Quispe-Aucca; Ricardo Romero-Loaiza; Nazario Villafuerte-Prudencio; Janette Rosario Ramos Pineda; José Martin Aguilar; Bernabé Canqui-Flores (Journal of the Selva Andina Biosphere)
The application of anaerobic biodigesters in municipal wastewater sludge is important for the generation of methane being an alternative for the generation of renewable energy, the research is peculiar because it is carried out at 3812 masl, in the area surrounding Lake Titicaca at a temperature variation between -1.3 to 16.8 °C. The objectives were: i) Design an anaerobic biodigester for methane generation and ii) Evaluate the amount of methane contained in the biogas generated by the LR of the three wastewater stabilization ponds. The methodology consisted of constructing a prototype design of an anaerobic biodigester with adequate performance for methane generation from sewage sludge (SWL), for which the biodigesters were loaded with 11 kg of SWL collected from three stabilization ponds. The results indicate that the anaerobic biodigester works adequately for methane generation, produced in the biodigesters, reached up to 36.7 % in 33 days of retention time at thermophilic temperature between 50 to 60 °C, the factors that influenced the low methane generation are the low C/N ratio and the low concentration of organic matter, which varied between 21.0 to 51.10 %.